Effects of levels of ensiled pineapple waste and pangola hay fed as roughage sources on feed intake, nutrient digestibility and ruminal fermentation of Southern Thai native cattle - Suchart Suksathit; Chalong Wachirapakorn; Yanin Opatpatanakit (Songklanakarin Journal of Science and Technology (SJST), 2011)
The objective of this experiment was to determine the effect of ensiled pineapple waste (P/A) as roughage source onrumen fermentation and feed utilization of native cattle. Four rumen-fistulated Southern Thai native cattle with initial weight286.1±48.5 kg were arranged to receive dietary treatments in a 4x4 Latin square design. Each period was lasted for 21 days.Cattle were fed concentrate to roughage at the ratio of 65:35. The roughage used was as follows; 1) 100% ensiled pineapplewaste, 2) 65% P/A and 35% pangola hay (HAY), 3) 35% P/A and 65% HAY and 4) 100% HAY. The results revealed that drymatter intake among dietary treatments was not significantly different (P>0.05) (3.70, 3.81, 3.52 and 3.59 kgDM/d). Apparentdigestibility of DM, OM, CP, NDF and ADF in cattle fed only P/A as roughage source was higher (P<0.05) than in cattle fedonly HAY. Increased HAY resulted in linearly decreased apparent digestibility of DM, OM, CP, NDF and ADF. Caloric densityof diet with only P/A as roughage source (2.96 Mcal/kgDM) was higher (P<0.05) than that of diet with only HAY (2.67 Mcal/kgDM). Ruminal temperature, pH and ammonia-nitrogen concentration were not different (P>0.05). Acetic acid, propionic acidand butyric acid concentrations were not significantly different (P>0.05) among dietary treatments. Blood urea-nitrogen wassimilar among dietary treatments. In conclusion, P/A is promising to use as a roughage source for Southern Thai native cattle.